Análisis del proceso de alfabetización pública a través de educa radio, como herramienta educomunicacional en el primer semestre de la pandemia COVID-19 en la parroquia Tarqui de Guayaquil - Icaza Alemán, Marissa Nicole (2022)
At present, study methods have been evolving, that is, it is no longer just being in front of a blackboard, but now technology, television and radio are being used for student teaching. The Covid-19 that affected all areas of knowledge, especially education, caused students to be unable to attend face-to-face classes, leading to virtual education and other educational tools. That is why the Ecuadorian state presented the Covid-19 Educational Plan, so that all students can have access to education either by radio or television. The general objective of this project is to analyze the public literacy process carried out by Educa Radio, as an educommunication tool during the first semester of the Covid-19 pandemic of the Battle of Tarqui Mixed Fiscal School in t he city of Guayaquil......